Case Report Series: Aggressive HR Deficient Colorectal Cancers Related to BRCA1 Pathogenic Germline Variants - Freire, Maria Valeria; Martin, Marie; Thissen, Romain; Van Marcke, Cédric; Segers, Karin; Sépulchre, Edith; Leroi, Natacha; Lété, Céline; Fasquelle, Corinne; Radermacher, Jean; Gokburun, Yeter; Collignon, Joelle; et al. (Frontiers in Oncology, 2022)
Objective The link between BRCA1 and homologous recombination deficiency (HRD) in cancer has gained importance with the emergence of new targeted cancer treatments, while the available data on the role of the gene in colorectal cancer (CRC) remain contradictory. The aim of this case series was to elucidate the role of known pathogenic BRCA1 variants in the development of CRC in young patients. Design Patients were evaluated using targeted next generation sequencing, exome sequencing and chromosomal microarray analysis of the paired germline and tumor samples. These results were used to calculate the HRD score and the frequency of mutational signatures in the tumors. Results Three patients with metastatic CRC were heterozygous for a previously known BRCA1 nonsense variant. All tumors showed remarkably high HRD scores, and the HRD-related signature 3 had the second highest contribution to the somatic pattern of variant accumulation in the samples (23% in 1 and 2, and 13% in sample 3). Conclusions A BRCA1 germline pathogenic variant can be involved in CRC development through HRD. Thus, BRCA1 testing should be considered in young patients with a personal history of microsatellite stable CRC as this could further allow a personalized treatment approach.